Librarians’ acceptance of open source Library Information System using the Osis-Utaut Model / Zainab Ajab Mohideen - Zainab Ajab, Mohideen (2017)
Research on technology acceptance is rapidly developing in multidisciplinary fields. Technology acceptance is focused either on users’ beliefs or for the betterment of system development. Both aspects are considered equally important to determine the users’ acceptance of a system. This research aims to investigate acceptance of open source library information system, like, Koha using an expanded UTAUT model called the OSIS-UTAUT model. The unified theory of acceptance (UTAUT) and use of technology model is applicable for both. The UTAUT model is widely used to test end-users’ ‘acceptance and use’ of a system, whereas the user acceptance test (UAT) focuses on functional and technical aspects of the system. In this study the UTAUT model is extended to include the system’s success, user skills and system cost aspects to measure librarians’ acceptance of Koha OSLIS (open source library information system). The proposed model known as the open source information system (OSIS). The model test the influence of system quality (SQ), information quality (IQ), Information technology skill (ITS) and cost (C) in addition to the constructs from UTAUT model, namely performance expectancy (PE), effort expectancy (EE), social influence (SI), self-efficacy (SE) and attitude towards using technology (ATUT). The survey instrument consist of 61 items representing all ten constructs. In the initial stage four expert validation of the survey instrument was performed. The respondents are Koha OSLIS librarians’ from selected academic libraries of public and private universities in Malaysia. A pre-test performed using the SPSS version 22 on a sample of 30 pioneer users’ of Koha OSLIS obtained a cronbach alpha’s value of > 0.7. The sample is considered moderately skewed-left hand tail with aleptokurtic distribution-heavier tail (kurtosis >0). A total of 215 responses were subjected to Partial Least Square (PLS) Professional version 3.0 software. Bootstrapping is performed to check the discriminant validity. Several items were removed and the final instrument has 56 items. The R2 value indicates a strong relationship between the variables and data used to build the proposed model. The R2 value of 79% represents the amount of variance in the dependent variable of user acceptance of Koha open source library information system is explained by the independent variables. Path analysis supported five of the proposed relationships, namely ATUT, PE, SQ, SI and IQ. Four other relationship, C, EE, ITS and SE were not supported for this dataset. This study contributes to the measure of user acceptance of open source library information system from both user behavioral aspect and system success aspect. The OSIS-UTAUT model is shown to be applicable for the measurement of librarians’ acceptance of Koha OSLIS. It is hoped this understanding will contribute to better management of OSLIS acceptance and use in academic libraries.